A High Voltage Generation And Measurement Techniques Of Alternating Current - Kristovel Ritonga; Muhammad Habib Agil; Roy Putra Andika Ambarita; Viktorman Waruwu; Solly Aryza (INFOKUM, 2025)
Isolation is the most important and inseparable thing in high voltage equipment. This isolation serves to separate two or more electrical conductors that are under voltage, so that there will be no electric jump or spark between the conductors. Air in normal conditions (air pressure 1013 mBar and temperature 20oC) has a certain breakdown voltage against high alternating voltage. Gas insulating materials, especially air, are insulating materials that are widely used in high voltage equipment because air in ideal conditions is a perfect insulator and is also the most widely used because it is easy, cheap and simple. In this test, room temperature conditions, conditions above and below room temperature are applied to ball-plane electrodes and needle-plane electrodes with different gap distances, to see how much influence the shape of the electrode, temperature, gap distance and voltage polarity have on the dielectric breakdown strength of air. Based on the measurement results at different gap distances, the characteristics of the increase in air breakdown voltage are obtained due to the influence of the gap distance between the two electrodes. The measurement results at different polarities show that the rougher, smaller and sharper electrodes with positive polarity will more easily release electrons. Keywords: insulation, air conditions, high voltage.